2014
DOI: 10.1038/sc.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

Relationship quality and perceived social support in persons with spinal cord injury

Abstract: Study design: This is a cross-sectional study. Objectives: The objective of this study was to examine the associations among the quality of couple relationship, perceived social support and health-related quality of life (HRQoL) in persons with spinal cord injury (SCI). Setting: The study was conducted in Italy. Methods: Forty-three persons with SCI were administered questionnaires for the evaluation of relationship quality (Dyadic Adjustment Scale), perceived social support (Multidimensional Scale of Perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The participants acknowledged that the support they received impacted positively on their adjustment to the injury. The need for social support for persons with SCI is well documented in the literature [51, 52]. Spousal support was identified by the participants who were married as the most important form of support, while the majority of the unmarried participants identified support from friends and family support as the most valuable form of support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants acknowledged that the support they received impacted positively on their adjustment to the injury. The need for social support for persons with SCI is well documented in the literature [51, 52]. Spousal support was identified by the participants who were married as the most important form of support, while the majority of the unmarried participants identified support from friends and family support as the most valuable form of support.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kalpakjian et al [53] reported on the importance of marriage to the wellbeing of persons with SCI and argued that being married was a facilitator for lower depressive symptoms and wellbeing among persons with SCI [53]. Similarly, in a cross-sectional survey, Tramonti and colleagues [52] identified couple and family support as the most important sources of support when compared with support from informal social networks such as friendships [52]. This implies that spousal and family support play a pivotal role among persons with SCI in the adjustment and adaptation to the injury.…”
Section: Discussionmentioning
confidence: 99%
“…An individual's state of health has been suggested to influence social participation and relationships for people with SCI, both positively [47, 58, 63, 72] and negatively [58]. Secondary impairments to body structure and function from SCI, including pressure injuries and pain, can be socially limiting, while general physical well-being will maximize social opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…Factors which were suggested to consolidate partner relationships after SCI included understanding, acceptance, and support from the non-SCI partner [16, 34, 72, 8082]; the presence of children, which leads to shared focus and purpose [34]; and spending quality time together and with family [34, 41]. The degree of social integration of persons with SCI was also associated with persistence of partner relationships over time [47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation